The Retropepsin-Type Protease APRc as a Novel Ig-Binding Protein and Moonlighting Immune Evasion Factor of Rickettsia - Curto, Pedro (2021)
Rickettsiae are obligate intracellular Gram-negative bacteria transmitted by arthropod vectors. Despite their reduced genomes, the function(s) of the majority of rickettsial proteins remains to be uncovered. APRc is a highly conserved retropepsin-type protease, suggested to act as a modulator of other rickettsial surface proteins with a role in adhesion/invasion. However, APRc's function(s) in bacterial pathogenesis and virulence remains unknown. This study demonstrates that APRc targets host serum components, combining nonimmune immunoglobulin (Ig)-binding activity with resistance to complement-mediated killing. We confirmed nonimmune human IgG binding in extracts of different rickettsial species and intact bacteria. Our results revealed that the soluble domain of APRc is capable of binding to human (h), mouse, and rabbit IgG and different classes of human Ig (IgG, IgM, and IgA) in a concentration-dependent manner. APRc-hIgG interaction was confirmed with total hIgG and normal human serum. APRc-hIgG displayed a binding affinity in the micromolar range. We provided evidence of interaction preferentially through the Fab region and confirmed that binding is independent of catalytic activity. Mapping the APRc region responsible for binding revealed the segment between amino acids 157 and 166 as one of the interacting regions. Furthermore, we demonstrated that expression of the full-length protease in Escherichia coli is sufficient to promote resistance to complement-mediated killing and that interaction with IgG contributes to serum resistance. Our findings position APRc as a novel Ig-binding protein and a novel moonlighting immune evasion factor of Rickettsia, contributing to the arsenal of virulence factors utilized by these intracellular pathogens to aid in host colonization. IMPORTANCE Many Rickettsia organisms are pathogenic to humans, causing severe infections, like Rocky Mountain spotted fever and Mediterranean spotted fever. However, immune evasion mechanisms and pathogenicity determinants in rickettsiae are far from being resolved. We provide evidence that the highly conserved rickettsial retropepsin-type protease APRc displays nonimmune immunoglobulin (Ig)-binding activity and participates in serum resistance. APRc emerges then as a novel Ig-binding protein from Gram-negative bacteria and the first to be identified in Rickettsia. Bacterial surface proteins capable of Ig binding are known to be multifunctional and key players in immune evasion. We demonstrate that APRc is also a novel moonlighting protein, exhibiting different actions on serum components and acting as a novel evasin. This work strengthens APRc as a virulence factor in Rickettsia and its significance as a potential therapeutic target. Our findings significantly contribute to a deeper understanding of the virulence strategies used by intracellular pathogens to subvert host immune responses.